In silico Studies on the anticancerigenic activities of Eugenol in the Indian Carnation (Syzygium aromaticum) (Research, Society and Development, 2021)
Objective: To investigate the anti-cancer properties of eugenol using In Silico methods. Methodology: it is an original article using the In silico methodology through PASS (Prediction of activity spectra for plants) software online and GUSAR available for free and acessful. Results: The results of the online PASS operating system demonstrated several positive biological activities, such as antimutagenic effect, caspase stimulant, pre-neoplasic treatment and apoptosis agonist having a probability of activity (BP) well above 0.700. Such findings reinforce the others in the literature that show an antineoplastic potential because the component has antioxidant effects, and is linked to an expression of genes involved in apoptosis and inflammation. Such as effects on the negative regulation of Bcl-2, COX-2 and IL-1ß, and actions on the positive regulation of P53, Bax and active expression of Caspase-3, caspase-9 in addition to inducing the pathway of mitochondrial apoptosis. As for the GUSAR software, toxicity was observed, demonstrating that in category 4, they are intravenous, oral, and subcutaneous routes of administration, indicating that it is not very toxic. In category 5, the intraperitoneal route is relatively non-toxic. This finding is still obscure and there are few scientific articles to support it. Conclusion: Eugenol has favorable effects for the treatment and prevention of various cancers and mutagenic cells, but there is still little knowledge about the toxicity of this component. Thus, it needs to go deeper into the theme.